Analisis Pendekatan Lingkungan Alam Sekitar Berbasis Saintifik Dalam Meningkatkan Motivasi Belajar IPA Siswa Kelas IV SD Negeri 101772 Tanjung Selamat - Widya Febrisah Widya; Sujarwo (PGSD UMN Al-Washliyah, 2021)
This study aims to increase motivation to learn science through a scientific-based approach to the natural environment on plant parts and their functions in grade IV SDN 101772 Tanjung Selamat, Kec. Percut Sei Tuan. This research is a qualitative research. The subjects of this study were fourth grade students, totaling 15 people and 1 teacher, namely the fourth grade homeroom teacher. Data collection techniques using observation, interviews and documentation. The data analysis technique used descriptive qualitative.How to increase students' motivation to learn science is by conducting learning in the environment around the school by utilizing plants as learning resources, dividing students into groups and then guiding students to make observations. The results showed that from the results of observations made by researchers, they saw that there were differences in the attitudes of students' enthusiasm for learning to be more active and enthusiastic when learning was carried out in the natural environment. And the results of student interviews showed that of the fifteen students who took part in learning in the natural environment, only two students did not like learning in the environment. This shows that learning by using the approach of the natural environment is a fun learning that can foster motivation in students towards learning.Keywords: Learning motivation, Environmental Approach